2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591325
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmography derivatives and pulse transit time in overnight blood pressure monitoring

Abstract: Overnight continuous blood pressure measurement provides simultaneous monitoring of blood pressure and sleep architecture. By this means, we are able to investigate whether different sleep events are associated to blood pressure fluctuations. In this paper, we used the Pulse Transit Time (PTT) to develop and evaluate functions for measurement of blood pressure. We focused on the first and second derivatives of fingertip Photoplethysmography (PPG) recordings to detect PPG critical points. By applying R wave of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 90%
See 1 more Smart Citation
“…M1 is the modality with the most data points and the strongest r. M1 is also the only category to include studies with sample sizes over 30, making the correlations stronger than those of studies with small sample sizes. Across most modalities, SBP estimations have consistently higher correlations with real SBP than DBP estimations do with real DBP [17,21,23,25,27,40,43,44,51,52,55,60,61,65,81,82]. Three studies from M2 [15], M1 [59], and M1 [67] showed the opposite trend and two studies from M1 [31] and M4 [20] reported the same r for both SBP and DBP.…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 90%
“…In more recent years, we see a rising trend in the emergence of new combinations of various biosignals (Figure 4). Of the 73 included studies, 22 reported the correlation (r) between estimated and reference BP for both SBP and DBP [15,17,20,21,23,25,27,29,31,40,43,44,51,52,55,[59][60][61]65,67,81,82]. Further, 15 studies reported the measurement variance in estimated versus reference BP for both SBP and DBP through mean error and standard deviation [21,22,33,34,38,51,59,60,64,67,69,72,78,82,83].…”
Section: Global Distribution and Combinations Of Biosignals Used In Lmentioning
confidence: 99%
“…Thus, using the acronym VPG (velocity of PPG) to describe the first derivative of the PPG waveform is a fitting name choice. Likewise, it is fitting to use the acronym APG (acceleration plethysmogram) to refer to the second derivative of the PPG signal, which provides the acceleration of blood flow in the fingers [ 7 ]. Note that the use of the acronym APG was recommended in [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The general relationship between BP and PTT was subject of a series of investigations. In [6,[14][15][16][17][18][19][20][21][22] different magnitudes for the computation of the PTT are based on the calculation of the time difference between the ECG R-peak and some reference within the PPG signal and are methodically described and validated by calculating a correlation to the IBP. In addition to the methodological aspects of the BP computation using the PTT, [23] also discusses the impact of influencing factors, like changes in individual arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%